International Dictionary of Marketing - Daniel Yadin (Kogan Page, 2002)
You will find this Dictionary very practical, with text designed as a guide on a dayto-day level. It can help you in two ways. First, it uses language that people actually speak, and helps to make clearer much of the jargon used in marketing. Two examples: you read in a marketing magazine about FMCG; but the author, assuming that everybody knows what this means, fails to explain it. The Dictionary comes to your aid. In a marketing textbook, you come across a term that the author uses and discusses, but which you still cannot fully appreciate. The Dictionary may help to resolve this. Second, on an even more pragmatic level, it explains marketing practices and procedures. You may, for example, be interested in how the monitoring of Web site hits is carried out. The Dictionary comes to the rescue by explaining ABC// electronic monitoring. Or, you may be undecided whether to use litho or flexography for a catalogue or brochure. The Dictionary helps you to make up your mind, and to understand what your printer is saying.